2020
DOI: 10.1016/j.jinf.2020.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Extraspinal articular tuberculosis: An 11-year retrospective study of demographic features and clinical outcomes in East London

Abstract: The global incidence of tuberculosis (TB) infection was estimated by the WHO to be 10 million cases in 2018, 85% of whom had pulmonary TB (pTB) infection (WHO 2019). In Europe, the extrapulmonary TB (EPTB) incidence is increasing, accounting for 22.6% of new cases reported in 2017 (ECDC 2019). Furthermore, the incidence of articular TB infections has risen in Europe (Jutte 2004, Lesic 2010. This is reflected in UK surveillance data, where in 2017, 2.2% of new TB cases presented with non-spinal bone infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The elbow is the most frequently affected joint in the upper extremity; accounting for 1e5% of all cases of skeletal TB. 5,24 Fan et al reported an incidence of 10.3% from the retrospective data, whilst a recent study by McGuire et al suggested elbow as the second-largest site (19.4%) of extrapulmonary tuberculosis after knee joint (23.7%) in their large cohort of cases 21,26…”
Section: Site and Incidencementioning
confidence: 98%
See 3 more Smart Citations
“…The elbow is the most frequently affected joint in the upper extremity; accounting for 1e5% of all cases of skeletal TB. 5,24 Fan et al reported an incidence of 10.3% from the retrospective data, whilst a recent study by McGuire et al suggested elbow as the second-largest site (19.4%) of extrapulmonary tuberculosis after knee joint (23.7%) in their large cohort of cases 21,26…”
Section: Site and Incidencementioning
confidence: 98%
“…17,22 Painful elbow due to early TB may also present as tennis elbow or a post-traumatic contusion leading to further delay in diagnosis. 21,28 Clinical manifestations can be constitutional and/or local. Constitutional features are present in about 20e30% of cases and may range from fatigue, evening rise of temperature, loss of appetite, loss of weight, and night sweats.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations